1997
DOI: 10.4141/a96-088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral administration of folate sources on plasma folate levels in pigs: Comparison between reduced and oxidized forms of folate

Abstract: . Effect of oral administration of folate sources on plasma folate levels in pigs: Comparison between reduced and oxidized forms of folate. Can. J. Anim. Sci. 77: [497][498][499][500][501][502]. Two experiments were conducted to evaluate the response of plasma folate levels after oral administration of oxidized or reduced forms of folates, using seven Göttingen minipigs. Plasma folate levels, tetrahydrofolate (THF) and 5-methyltetrahydrofolate (5CH 3 -THF), were determined by high-performance liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
1
Order By: Relevance
“…These findings from in vivo and in vitro experiments demonstrate that the DHFR activity for PteGlu in pigs was much less than that in rats. The low DHFR activity in pigs may be one of the causal factors of the fact that the plasma H4PteGlu and 5-CH3-H4PteGlu did not in crease after oral administration of PteGlu, even at high dose (4,13). The reduction of PteGlu to H2PteGlu in pigs may be regarded as the rate-limiting step for the re duction of PteGlu to H4PteGlu, because the Vmax of pig liver DHFR for PteGlu was remarkably small, compared with that for H2PteGlu ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…These findings from in vivo and in vitro experiments demonstrate that the DHFR activity for PteGlu in pigs was much less than that in rats. The low DHFR activity in pigs may be one of the causal factors of the fact that the plasma H4PteGlu and 5-CH3-H4PteGlu did not in crease after oral administration of PteGlu, even at high dose (4,13). The reduction of PteGlu to H2PteGlu in pigs may be regarded as the rate-limiting step for the re duction of PteGlu to H4PteGlu, because the Vmax of pig liver DHFR for PteGlu was remarkably small, compared with that for H2PteGlu ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Esses pesquisadores sugeriram três hipóteses para esse evento e que podem também justificar a tendência de diminuição do folato sérico neste experimento: 1) inibição competitiva na absorção intestinal do ácido fólico com folatos endógenos derivados da circulação enterohepática, visto que grandes quantidades de folatos endógenos são recicladas por esta circulação (Steinberg, 1984;Shin et al, 1995) e absorvidas ativamente na mucosa intestinal; 2) competição de ligação do ácido fólico sobre o tetrahidrofolato para a proteína de ligação de folato no plasma (o ácido fólico entrando no sistema circulatório pode libertar tetrahidrofolato do sítio de ligação de proteína de ligação de folatos, expondo o tetrahidrofolato à possível degradação na circulação e/ou melhorando a eficiência renal de liberação de tetrahidrofolato); e 3) reduzida conversão de ácido fólico para folato reduzido, ou seja, baixa atividade de folato redutas no fígado de suínos, uma vez que administração de dihidrifolato aumenta os níveis de folatos no plasma, o que não ocorre com o ácido fólico (Mizuno et al, 1997). Essas hipóteses também podem ser apontadas para justificar a ausência de correlação entre os valores de folato sérico e o aumento de suplementação de ácido fólico neste experimento, uma vez que a metodologia empregada quantifica folatos totais e não especifica as formas oxidadas e reduzidas.…”
Section: Adwg (Kg)unclassified
“…It is possible that intestinal reduction of folates is more efficient under limit-feeding conditions, but this point cannot be determined from these data. Using mature, nonpregnant miniature pigs, Mizuno et al (1997) have presented data indicating that oral supplements of THFA and a bacterial cell powder rich in reduced folates were more effective than pteroylmonoglutamate (oxidized) folate in elevating plasma THF. Furthermore, it has been demonstrated in rats that intestinal absorption of 5-MF is inhibited by the pteroylmonoglutamate form of the vitamin (Kudo et al, 1995).…”
Section: Plasma Reduced Folates-sowsmentioning
confidence: 99%
“…In previous studies, the oxidized or pteroylmonoglutamate form of the vitamin has been used, but in vivo, the reduced forms dihydrofolate and tetrahydrofolate function in single-carbon transfer reactions for nucleic acid synthesis and amino acid metabolism (Krumdieck, 1990). Mizuno et al (1997) reported that oral supplementation of pigs with tetrahydrofolic acid or a bacterial cell powder rich in reduced folates was more effective than an oxidized source in elevating plasma reduced folates. Considering these factors, reduced sources of supplemental folate may produce greater litter size responses in sows than the pteroylmonoglutamate traditionally supplemented.…”
Section: Introductionmentioning
confidence: 99%